Grundrisse : Introduction to Marx’s Political Economy and Historical Materialism - Raju Das (World Review of Political Economy, 2024)
This article systematically presents Marx’s ideas about political economy and historical materialism in the “Introduction” to the Grundrisse . Two questions are posed and addressed. The first one is: what implications does the “Introduction” have for the contemporary Marxist discussions on economic crisis, and on primitive accumulation? Underlying these two topics is the question of the importance of production relative to distribution, exchange and consumption. Marx sometimes appears to be ambivalent in his treatment of this question, and this partly explains why some Marxists can suggest that the production of commodities under capitalism is not the main aspect of late capitalism, and find the main reason for economic crisis outside of production. Read carefully, however, the “Introduction” does provide enough ground to critique these views. The second question addressed is: what implications might Marx’s discussion on political economy and historical materialism, including the relation between culture and economic development, have for the fight for socialism?